2021
DOI: 10.1038/s41598-021-94738-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations of apparent temperature with acute cardiac events and subtypes of acute coronary syndromes in Beijing, China

Abstract: Limited evidence is available on apparent temperature (AT) and hospital admissions for acute cardiac events. We examined the associations of AT with admissions for acute cardiac events and acute coronary syndrome (ACS), and explored the effect difference between ST-elevation myocardial infarction (STEMI) and non-ST-elevation myocardial infarction ACS (NSTE-ACS). Poisson regression with distributed lag non-linear model was applied to examine the temperature-lag-admission associations. Stratified analyses were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
1
9
0
1
Order By: Relevance
“…This association between low temperatures and AAD risk (with lags of 0 to 7 days) was detected even with a long heating period during winter in cold regions. This result aligns with previous findings of associations between low ambient temperature and a high risk of acute cardiovascular incidents, such as acute coronary syndrome, heart failure, hypertension, and stroke (25)(26)(27)(28)(29). In addition, the risk of AAD increased with lower ambient temperature to a greater extent than the risks of the cardiovascular events listed above.…”
Section: Discussionsupporting
confidence: 91%
“…This association between low temperatures and AAD risk (with lags of 0 to 7 days) was detected even with a long heating period during winter in cold regions. This result aligns with previous findings of associations between low ambient temperature and a high risk of acute cardiovascular incidents, such as acute coronary syndrome, heart failure, hypertension, and stroke (25)(26)(27)(28)(29). In addition, the risk of AAD increased with lower ambient temperature to a greater extent than the risks of the cardiovascular events listed above.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, other data suggested a significant correlation between the frequent occurrence of AMI and decreased air temperature, along with heightened atmospheric pressure, low humidity, and prolonged sunshine duration [ 33 ]. Reports from a study in China revealed an uptick in the number of STEMI hospitalizations during periods of high apparent temperatures and an increased incidence of NSTEMI on days with low apparent temperatures [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most current studies reported that extremely high temperatures increased the risk of CVD admission. For example, in Beijing, the cumulative effect of high apparent temperature on ST segment elevation myocardial infarction related admissions reached a peak relative risk of 2.55 (95% CI: 1.02–6.38) in lag 0–6 days [ 48 ]. A 272 main Chinese cities time serials study found a relative risk of mortality from cardiovascular disease associated with extreme high temperature was 1.22 (95% CI: 1.16–1.28) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%